Konsep Estetika Jepang: Corak Naturalis yang Dijiwai oleh Tradisi, Kepercayaan, dan Alam - Kartini Parmono (Jurnal Filsafat "WISDOM", 1999)
The Japanese Aesthetics concept is a blend of traditions, beliefs, and nature. This research was conducting by studying literature and the collected was analyzed by using interpretation method.The result of the study that the starting point of the Japanese Aesthetics is nature. Japanese believe that daily natural phenomenon such as sun, moon, mountain, water fail, and trees is believed to have or souls "kami". The nature is not only the place where masters strengthen receive the spirit and the meaning of life. The existing religion belief of Japanese (Shinto and Budha) provide the drive for their followers to be closer to the nature. According to the Shinto belief, the nature is full of the souls of human predecessors that there are an obligation to conservate the nature and to keep it in a harmony. It is proven by Japanese deep loving emotion and understanding of seasonal changes.Budhist beliefs spreads out in Japan with special characteristic wllkwon as Budhist Zen. Budhist Zen results in Japanese customs and traditions such as the ceremony of tea drinking considered to be sacred just in the sam cultural position as another religious rituals. The influence of the Budhist Zen in military area enables the new cultural group called Samurai to emerg in the spirit Bushido. The Samurai group is symbolized with Sakura flowers (the most beautiful flowers in Japan) willing to early die in the devotion for their king.The Japanese artistic works are naturalistic (resembling nature). Thus, Japanese always want to be close to nature and to live in a harmony with the nature.